2021
DOI: 10.3389/fendo.2021.707726
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated Subacute Thyroiditis: Evidence-Based Data From a Systematic Review

Abstract: Subacute thyroiditis (SAT) is a thyroid disease of viral or post-viral origin. Whether SAT represents a complication of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is still unclear. Our aim was to systematically review the literature to 1) explore the size of the literature about SAT in COVID-19 and 2) evaluate the clinical characteristics of SAT. PubMed/MEDLINE, Embase, and Scopus were searched until April 20, 2021. Original papers, case reports, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
80
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 60 publications
9
80
2
Order By: Relevance
“…There is some evidence of thyroid dysfunction in patients with COVID-19, characterized by changes in hormone levels (low triiodothyronine or low thyrotropin levels) or laboratory results compatible with the presence of subacute thyroiditis [15,19]. Italian researchers observed that in the spring of 2020, 15% of COVID-19 patients (n=93) admitted to the intensive care unit (ICU) at a hospital in Milan had changes in thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of thyroid dysfunction in patients with COVID-19, characterized by changes in hormone levels (low triiodothyronine or low thyrotropin levels) or laboratory results compatible with the presence of subacute thyroiditis [15,19]. Italian researchers observed that in the spring of 2020, 15% of COVID-19 patients (n=93) admitted to the intensive care unit (ICU) at a hospital in Milan had changes in thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Main viruses associated with SAT are coxsackievirus A and B, echovirus, mumps, measles, influenza. Shortly after the onset of SARS-CoV-2 pandemic, many cases of SAT induced by this virus have been described [ 2 6 ]. Direct evidence of viral presence in the thyroid gland has been indeed demonstrated for several viruses [ 7 ], including SARS-CoV-2 [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of SARS-CoV-2-associated SAT cases, it was commented that the clinical features did not differ from classical SAT [ 46 ]. Consistent with this interpretation, in our study, CoV-SAT and NonCoV-SAT groups were similar regarding clinical features, laboratory findings and treatment characteristics.…”
Section: Discussionmentioning
confidence: 99%